ANALISIS PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP KEBIJAKAN DEVIDEN PADA SEKTOR INDUSTRI MANUFAKTUR DI BEI - Perdana, Buyung Cahya (Universitas PGRI Adi Buana, 2018)
The purpose of this study is to empirically study the effect of accounting variables – liquidity ratio, leverage and profitability ratio - on research is to examine the factors which is influence Dividend Policy in manufactur sector of Bursa Efek Indonesia (BEI). The research use fundamental factors of company: financial ratio which is liquidity ratio represent by Current Ratio (CR), leverage ratio represent by Debt to Equity Ratio (DER), profitability ratio represent by Return on Investment (ROI), as independent variable and dependent variable Dividen Policy represent by Dividend Payout Ratio (DPR). The result of research indicate that the fundamental ratio which is consist of Current Ratio, Debt to Equity Ratio and Return on Investment are together have significant effect to Dividen Payout Ratio. The result also indicate that Current Ratio variable and Return on Investment variable is partiality have positive and significant effect to Dividen Payout Ratio, but Debt to Equity Ratio has no significant effect to Divident Payout Ratio.